Effects of Indomethacin on Patent Ductus Arteriosus in Neonates with Genetic Disorders and/or Congenital Anomalies - Takami, Takeshi; Yoda, Hitoshi; Ishida, Takehiko; Morichi, Shinichiro; Kondo, Atushi; Sunohara, Daisuke; Hoshika, Akinori; Kawakami, Tadashi (American Journal of Perinatology, 2013)
Objectives The study aimed to evaluate the effectiveness of intravenous indomethacin (IND) therapy for patent ductus arteriosus (PDA) in neonates with genetic disorders and/or congenital anomalies soon after birth.Study Design A total of 301 neonates with a genetic disorder and/or congenital anomalies and with a gestational age of ≥35 weeks were admitted during the study period. Eighty-five neonates with 56 genetic disorders (30 cases of trisomy 21, 10 cases of trisomy 18, and 16 others) and 29 congenital anomalies, and with clinical symptoms received intravenous IND therapy. The management methods were similar to those used for PDA in low-birth-weight infants.Results IND therapy had a clinical benefit at a high rate of 79% in these patients (90% and 70% in neonates with trisomies 21 and 18, respectively), including complete closure of the PDA in 52% of the patients. Although oliguria was observed in 43 infants (51%) and slight gastrointestinal bleeding was observed in 12 (14%), no infants had severe complications such as intracranial bleeding.Conclusions IND therapy is an effective treatment option before considering surgery for PDA in neonates with genetic disorders and/or congenital anomalies. This therapy may reduce the difficulty of treatment in the acute stage among these neonates.
Keywords: patent ductus arteriosus (PDA); indomethacin; chromosome abnormality; trisomy 21; trisomy 18